Radiological hip indices correlate with GMFCS level I and GMFM-66 scores in cerebral pasy - Elvan, Özlem; Keskinbora, Mert; Çelikcan, Havva; Bobuş, Alev; Özgür, Anıl; Kömür, Mustafa; Kurtoğlu Olgunus, Zeliha (My University, 2019)
Objectives: The aim of this study was to evaluate the certain radiological hip parameters and the effects of these parameters on the functional capacity of cerebral palsy (CP) children, to compare the Gross Motor Function Measure (GMFM-66 scores) of hemiparetic and diparetic children with spastic CP in Gross Motor Function Classification System (GMFCS) level 1, and to define possible differences or similarities with the control group. Methods: The radiographic parameters measured for CP and control groups were caput-collum-diaphyseal angle (CCD), migration index (MI), center edge angle (CEA), acetabular index (AI) and pelvic obliquity. The functional capacity of the CP group was assessed by GMFM-66. Results: No significant differences were found in terms of sides of the same individual in each group. Significant differences were found between groups for left CCD, right MI, right and left AI, and right and left CEA. Correlation analyses revealed significant relationships between radiological parameters. Hemiparetics had statistically higher GMFM-66 dimension E score than diparetics. Conclusion: The threshold values for hip parameters were determined with CP in GMFCS level 1. The hemiparetic and diparetic children with CP, who were at the GMFCS level I and age group, had similar hip morphology. Development of femoral head and acetabulum in these children were not different from control group. Evaluating the functional levels of patients according to GMFM-66 scores with radiographic parameters is believed to contribute to the monitoring CP children.
Keywords: Cerebral Palsy; Functional Capacity; Gross Motor Functional Classification System; Gross Motor Function Measure; Radiographic Hip Parameters